Paralinguistic Features of Students` â€œPinocchioâ€ Story Telling Dealing with Speaking Ability - Triwardani, Henni Rosa (Jurnal Ilmiah Dozen Globalindo, 2021)
Paralinguistic deals with nonverbal language to convey meaning or message. But in some cases, students still have weaknesses to build this in their story telling activity. They fail to use both physical and vocal paralinguistic to support their message. Involving students of Early Childhood Education Teacher (PGPAUD) at first grade in Al-Ihya Islamic University of Kuningan as subject research, this study tends to know students capability in using paralinguistic features and the role of paralinguistic features in delivering meaningfull message in doing story telling. As qualitative research, data were gathered from the record of students` story telling entitled â€œPinocchioâ€ and observation sheet which were then analized by descriptive analysis method. The result showed, students` capability was very poor, they failed in using paralinguistic features to deliver message through spoken language or story telling. Mostly were physical paralinguistic such as facial expression, gesture , and the highest was posture and also found that paralinguistic features played role to the success and the failure of students` story telling activity. For the next research, researcher should focus on building students paralinguistic features through dubmash or another method relates to the use of technology in EFL context.